2014
DOI: 10.1097/brs.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the French-Canadian Version of the Scoliosis Research Society 22 Questionnaire in France

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
0
18
0
2
Order By: Relevance
“…For each patient, the following demographic data were recorded: age, sex, body mass index (BMI). Different healthrelated quality of life scores (HRQOL) were collected: the Oswestry disability index (ODI), the Scoliosis Research Society 30 (SRS30) and the Short Form 12 mental and physical component (SF12-MCS and SF12-PCS), visual analog scale for lumbar pain (VAS-L) [13][14][15][16][17].…”
Section: Demographic and Clinical Datamentioning
confidence: 99%
“…For each patient, the following demographic data were recorded: age, sex, body mass index (BMI). Different healthrelated quality of life scores (HRQOL) were collected: the Oswestry disability index (ODI), the Scoliosis Research Society 30 (SRS30) and the Short Form 12 mental and physical component (SF12-MCS and SF12-PCS), visual analog scale for lumbar pain (VAS-L) [13][14][15][16][17].…”
Section: Demographic and Clinical Datamentioning
confidence: 99%
“…The original SRS-22 questionnaire is currently widely utilised to assess HRQoL in adolescents with scoliosis, [1026, 30, 34–41] but the findings of the present study indicate that our revised SRS-18fv may be more appropriate for the French-Canadian adolescent population.…”
Section: Discussionmentioning
confidence: 68%
“…Other studies of the original SRS-22 and SRS-22fv also reported Cronbach alpha values for the function factor that fell below the accepted value. [12, 26, 30, 35, 39] This suboptimal level of internal consistency suggests that items within this component may not all be clearly tapping the same construct. The lack of clear conceptual delineation might arise from the inclusion of terms like “labor” and “work” in the phrasing of the items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Для определения внутренней согласованности анкеты использовали показатель альфа Кронбаха, при котором сравнивается разброс каждого элемента с общим разбросом всей шкалы [4]. Применяли метод вариационной статистики: вычисление средней арифметической (М) и среднего отклонения (±m), коэффициент корреляции r-Пирсона с оценкой по шкале Чеддока, для оценки достоверности различия средних использовали t-критерий Стьюдента с опре- гих странах и получила международное признание [7,19,21,22,24,25,27]. Деформации позвоночника у взрослых характеризуются повышенным уровнем инвалидизации, включая боль и нарушение функции, а также изменением самовосприятия и психического здоровья [12,14,17,31] Внутренняя согласованность анкетных опросников определяется связью каждого конкретного элемента теста с общим результатом, с тем, насколько каждый элемент входит в противоречие с остальными, а каждый отдельный вопрос измеряет признак, на который направлен весь тест.…”
Section: материал и методыunclassified